Assessment of Urban Renenewal Studies in the Context of Florence's Old Industrial Sites - Elif Özlem Aydın (Konya Technical University Faculty of Architecture and Design, 2013)
In the periphery of the historic city center of Florence, which is a settlement in Middle Italy, considered the symbol of Renaissance period train stations, small scale industrial structures were built under the influence of spread of industrialization in Continental Europe in the 19th century. Industrial buildings whose original functions are being lost nowadays are restricted to examples which started being built in the 18 th century, however, shaped in the 19 th century and were being able to brought until today with the increased industrialization activities in the first half of the 20 th century. The necessity of developing new thoughts aiming to revitalize areas around the city center and to reshape Florence, which witnessed a segmented growth due to increased industrialization in the first half of 20 th century, according to urban planning principles from 1990's onwards has been realized. Within the scope of integrated planning developed in the recent years, old industrial areas located in the historical city center peripheries whose functions have been lost are determined as urban renovation sites. In this study, Old Leopolda Train Station, Fiat Belfiore and Fiat Novoli factory sites as well as renovation/transformation work executed in old slaughter house sites, located in the west border of historical city center of Florence, have been studied with the help of technical surveys, personal interviews or published projects. Two approaches have been encountered when urban renovation projects executed in these areas where mixed-use strategies are adopted are examined. These are:  Preservation of some of the historical structures in the area, and demolition of some to create areas for new uses,  Demolition of all structures in the site to create areas for new uses. Not encountered in Florence, but there also exist renovation examples where almost all structures in the area are preserved. The results of research and observations have shown that three approaches are preferred in the renovation/transformation of old industrial areas. It has been concluded that, like in the example of Florence, there is a lack of methodology in the selection of these approaches adopted for various reasons. In fact, it is possible to talk about various parameters in the adoption process of this selection. The parameters determined after observations can be enumerated as:  Benefit-damage relationship of “preservation, re- functioning,  demolition” of structures in the site in national, regional and  urban scale,  Social environment needs and properties,  Land use value of the site,  Use value of structures in the site. The necessities of determining the basic parameters about the site as listed above and of setting up a methodology according to which the relationship of these parameters among themselves can be evaluated healthily in the adoption process of renovation approach have been understood. This methodological approach will contribute to the acceptable reestablishment of weakened spatial and social connections between the city centers and areas in the peripheries of the cities.